The ex-votos as media in the transmission and in the preservation of social memory (Revista Internacional de Folkcomunicação, 2021)
This article, of a theoretical nature, based on a bibliographical research, grounded on the studies in Folkcommunication, with the theories of Luiz Beltrão, and on the notion of religious cultural memory, with the emphasis defended by Jan Assmann, puts attention to the communicative character of the religious memory that encompasses the articulation of lived experiences and transmitted learning. The ex-votos are highlighted in the study, a common practice of various religious groups, of thanks for a divine grace achieved, interpreted here as vehicles of transmission and preservation of the memory of a locality and an time. In the methodological course, an application is elaborated, through the presentation of the extension of the typologies used in the studies of Folkcommunication, proposed in a doctoral dissertation defended by one of the authors of this study, as the indication of possible forms of transmission and preservation of social memory in each type of ex-votos. Religious cultural memory; Folkcommunication; Ex-votos.